Animasi Edukasi Interaktif Tes Kemampuan Konsentrasi Dengan Permainan Tebak Warna - Suhar Janti (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
The ability of the school to attract new students to gain knowledge in school requires in its implementation strategy. Junior high school Hang Tuah 1 North Jakarta which is a private school has a new admissions system selection is quite diverse, one satuya tests students' ability to concentrate. The need for fresh ideas to provide an interesting learning test media is needed junior high school Hang Tuah 1. One of the media in the form of multimedia learning through games is a fresh idea in the implementation of new admissions test selection this. By using the method of water fall in researching the problems and needs of the system of selection of new admissions test this, the importance of this study is able to implement an interactive educational animation application that makes the test more interesting students' ability to concentrate that can be used as a method of learning to new students.